Analytical study of tessellated structural-architectural reinforced concrete shear walls. (1st October 2021) - Syed, Mohammad; Moeini, Mohammad; Okumus, Pinar; Elhami-Khorasani, Negar; Ross, Brandon E.; Kleiss, Michael Carlos Barrios
Highlights: Validation of analysis methods. Comparison of tessellated and conventional shear walls. Analyses of tessellated walls with varying edge tile patterns. Damage definitions and quantification for aiding designers. Parametric study involving parameters like concrete strength and reinforcement ratio. A simplified analytical model to estimate the capacity of tessellated shear walls. Abstract: This paper studies the lateral behavior of a reinforced concrete tessellated structural-architectural (TeSA) shear wall system. TeSA walls are made of prefabricated repetitive tiles and have the ability to localize damage which occurs under extreme loading. A TeSA wall is intended for architectural interest, automated construction, reconfiguration, disassembly, and reuse. This study focuses on TeSA tiles that are topologically interlocking in two directions. Nonlinear finite element analysis is used to study the monotonic pushover behavior of TeSA walls with different edge tile configurations and a comparison is made thereof with a conventional reinforced concrete shear wall. The results indicate that the strength of TeSA walls is not significantly affected by the configuration of edge tiles. Damage progression in tiles and the number of damaged tiles that need to be replaced are also presented at different drift ratios. The study shows that reinforcement ratio substantially affects the wall lateral capacity. Finally, a simplified cross-sectional analysis procedure is proposed to provide a lower and upper bound estimate of the lateral capacity of TeSA walls.